Caracterização e aceitabilidade de tomate seco - Munhoz, Cláudia Leite; Umebara, Tiemi; Branco, Ivanise Guilherme [UNESP]; Sanginez-Argandoña, Eliana Janet (Universidade Tecnologica Federal do Parana (UTFPR), 2011)
In this work evaluated the content of vitamin C and total carotenoid in tomatoes fresh and dehydrated for conserve, with posterior immersion in sauce, verifying its sensorial acceptability. Dehydration was performed in dryer with airflow at 70 °C to obtain a product with final moisture of 45%. Determinations were carried out ascorbic acid, soluble solids, acidity, sugars and carotenoid before and after the dehydration process. The dehydrated tomatoes had been immersed in three types of sauces (pepper sauce, oregano with parrot leaves sauce and garlic sauce) per 25 days. After this period, the dry tomatoes in conserve had been submitted to the sensorial analysis in the pate form, applying themselves preference test. The results had been showed that retention of vitamin C and total carotenoid in the dehydrated product showed retention of 14.0% and 44.3%, respectively, in tomatoes after the dehydration process. Among the formulation of canned t

Neste trabalho avaliou-se o conteúdo de vitamina C e de carotenóides totais em tomates frescos e desidratados para conserva, com posterior imersão em molho para avaliar sua preferência e aceitabilidade sensorial. A desidratação foi realizada em secador com fluxo de ar a 70 °C até obtenção de um produto com umidade final de 45%. Foram realizadas determinações de ácido ascórbico, sólidos solúveis, acidez, açúcares e carotenóides totais antes e após o processo de desidratação. Os tomates desidratados foram imersos em três tipos de molhos (de pimenta, de orégano com folhas de louro e de alho) por 25 dias. Após esse período, os tomates secos em conserva foram submetidos à análise sensorial na forma de patês, aplicando-se teste de preferência. Os resultados mostraram que houve retenção de vitamina C e de carotenóides totais de 14,0% e 44,3%, respectivamente, no tomate após o processo de desidratação. Dentre as formulações de conserva verificou-se que não houve diferença sensorial significativa ao nível de 5% entre os patês, sendo todas as formulações aceitas.
Characterization and acceptance of dried tomato
Keywords: Lycopersicon esculentum Mill; Sensorial analysis; Dry tomato; Vitamin C; Carotenoid; Lycopersicum esculentum Mill; Análise sensorial; Tomate seco; Vitamina C; Carotenóides